Potensi pemberian yoghurt sinbiotik berbahan baku ubi jalar ungu terhadap jumlah e. coli pada feses tikus wistar - Jayanthi Petronela Janggu; B Wirjatmadi; Merryana Adriani; Reineldis Trisnawati (ARGIPA (Arsip Gizi dan Pangan), 2021)
The number of pathogenic bacteria Escherichia coli which increases in the digestive tract can cause infectious diseases in humans. One of the pathogenic bacteria in the digestive tract, especially the small intestine, which often causes digestive disorders is Enteropathogenic Escherichia coli (EPEC). EPEC bacteria in the digestive tract can damage the intestinal mucosa causing infectious diseases in humans. This study aimed to determine the effect of synbiotic yogurt (made from Lactobacillus bulgaricus, Streptococcus thermophilus, Bifidobacterium bifidum and purple sweet potato juice) on the number of E. coli in mice. A total of 24 male wistar rats were used in this study which consisted of 4 groups, namely (1) negative control, (2) positive control, (3) synbiotic yogurt, (4) synbiotic yogurt + EPEC. Yogurt was given orally using a sonde from day 1 to 21, with a population of lactic acid bacteria 107 CFU / ml. EPEC infection was carried out orally using a sonde from day 8 to 14, with a population of 106 CFU/ml. On the 22nd day, rat feces were collected and the number of bacterial colonies identified as E. coli was carried out on Mac Conkey Agar (MCA) selective media with a Spread Count Method. EPEC infection caused diarrhea, both in the positive control group mice and the synbiotic yogurt + EPEC group. The positive control group of rats had the highest number of E. coli colonies and was significantly different from the other groups of mice. Giving synbiotic yogurt (both in the synbiotic yogurt group and the synbiotic yogurt group + EPEC), significantly decreased the number of E. coli colonies in mice). Synbiotic yogurt can prevent diarrhea.